1977
DOI: 10.4039/ent1091109-8
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Assessment of the Potential of 16 Experimental Compounds as Soil Insecticides

Abstract: The effectiveness of 16 experimental compounds as soil insecticides was assessed under laboratory conditions. Chlorpyrifos, carbofuran, and dieldrin were included as standard insecticides. Spectrum of activity as contact insecticides was determined using 24–48 h nymphs of the field cricket, Acheta pennsylvanicus (Burmeister), 24–48 h onion maggot adults, Hylemya antiqua (Meigen), third stage darksided cutworms, Euxoa messoria (Harris), northern corn rootworm adults, Diabrotica longicornis (Say), and honeybees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
(3 reference statements)
1
8
0
Order By: Relevance
“…The efficacy of chlorpyrifos was reduced in soils with high organic matter content, but pH had no effect on toxicity (Whitney 1967). Harris and Turnbull (1977) found that chlorpyrifos, carbofuran, and terbufos were approximately 30 times more effective in moist sand than in moist muck. In summary, there is overwhelming evidence indicating that soil type greatly influences toxicity.…”
Section: Universify Microfilms Internationalmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of chlorpyrifos was reduced in soils with high organic matter content, but pH had no effect on toxicity (Whitney 1967). Harris and Turnbull (1977) found that chlorpyrifos, carbofuran, and terbufos were approximately 30 times more effective in moist sand than in moist muck. In summary, there is overwhelming evidence indicating that soil type greatly influences toxicity.…”
Section: Universify Microfilms Internationalmentioning
confidence: 99%
“…Temperature effects on insecticidal activity in soil may be less dramatic than soil moisture, but Harris and Turnbull (1977) showed positive temperature coefficients for many insecticides ranging from 3 to 30 times more effective at 32°C than at 16°C. Presumably, because adsorption is an exothermic process, higher temperatures favor desorption and increased availability of the insecticide (Harris 1972).…”
Section: Universify Microfilms Internationalmentioning
confidence: 99%
“…A previous study (Harris and Turnbull 1977) in which the potential of a number of experimental compounds as soil insecticides was assessed under laboratory conditions indicated that the biological activity of chlorpyrifos-methyl and CounterB was sufficiently promising to warrant more detailed study. Chlorpyrifos-methyl is similar in chemical structure to chlorpyrifos, the former being the 0,O-dimethyl, the latter the 0,O-diethyl form of 0-(3,5,6-trichloro-2-pyridyl) phosphorothioate.…”
Section: Introductionmentioning
confidence: 99%
“…The β-lactam ring shows various biological activities such as antifungal [7,8], antibacterial [9,10], antitubercular [11,12], anticonvulsant [13], analgesic, anti-inflammatory [14], synthetic precursor for amino acids [15], antiviral [16] and many more. Variety of heterocyclic products including drugs [17,18], dyes and intermediates such as thiazol yellow, thioflavin T., thidiazuron [19], herbicides [20], insecticides [21,22] and many more attributed to possess thiazolidin-4-one.…”
mentioning
confidence: 99%